VU0810464, a non‐urea G protein‐gated inwardly rectifying K+ (Kir3/GIRK) channel activator, exhibits enhanced selectivity for neuronal Kir3 channels and reduces stress‐induced hyperthermia in mice. (30th May 2019) - Vo, Baovi N.; Abney, Kristopher K.; Anderson, Allison; Marron Fernandez de Velasco, Ezequiel; Benneyworth, Michael A.; Daniels, John Scott; Morrison, Ryan D.; Hopkins, Corey R.; Weaver, Charles David; Wickman, Kevin
Abstract : Background and Purpose: G protein‐gated inwardly rectifying K + (Kir 3) channels moderate the activity of excitable cells and have been implicated in neurological disorders and cardiac arrhythmias. Most neuronal Kir 3 channels consist of Kir 3.1 and Kir 3.2 subtypes, while cardiac Kir 3 channels consist of Kir 3.1 and Kir 3.4 subtypes. Previously, we identified a family of urea‐containing Kir 3 channel activators, but these molecules exhibit suboptimal pharmacokinetic properties and modest selectivity for Kir 3.1/3.2 relative to Kir 3.1/3.4 channels. Here, we characterize a non‐urea activator, VU0810464, which displays nanomolar potency as a Kir 3.1/3.2 activator, improved selectivity for neuronal Kir 3 channels, and improved brain penetration. Experimental Approach: We used whole‐cell electrophysiology to measure the efficacy and potency of VU0810464 in neurons and the selectivity of VU0810464 for neuronal and cardiac Kir 3 channel subtypes. We tested VU0810464 in vivo in stress‐induced hyperthermia and elevated plus maze paradigms. Parallel studies with ML297, the prototypical activator of Kir 3.1‐containing Kir 3 channels, were performed to permit direct comparisons. Key Results: VU0810464 and ML297 exhibited comparable efficacy and potency as neuronal Kir 3 channel activators, but VU0810464 was more selective for neuronal Kir 3 channels. VU0810464, like ML297, reduced stress‐induced hyperthermia in a Kir 3‐dependent manner in mice. ML297, but not VU0810464, decreased anxiety‐related behaviour as assessed with the elevated plus maze test. Conclusion and Implications: VU0810464 represents a new class of Kir 3 channel activator with enhanced selectivity for Kir 3.1/3.2 channels. VU0810464 may be useful for examining Kir 3.1/3.2 channel contributions to complex behaviours and for probing the potential of Kir 3 channel‐dependent manipulations to treat neurological disorders.